Small intestine histologic neuronal features of type-2 diabetes mellitus rats treated with ethanolic extract red betel leaf (Piper crocatum) nanoparticle (EERbLNp) - Tri Wahyu Pangestiningsih; Roza Azizah Primatika; Teguh Budipitojo; Woro Danur Wendo (Universitas Sebelas Maret, 2023)
Objective: This study marked histological features of small intestine neurons in the type-2 diabetes mellitus (T2DM) rat model treated with ethanolic extract red betel leaf nanoparticle (EERbLNp)Methods: Thirty male Wistar rats were allotted into five groups (six rats each). Group I is nondiabetic control; group II is streptozotocin-nicotinamide (STZ-NA)-induced T2DM; group III-V are the STZ-NA-induced T2DM treated daily per oral with EERbL-Np at the doses 30, 60, and 90 mg/kg, respectively, within 28days. The duodenum, jejunum, and ileum were collected for routine histological staining and cresyl violet special staining to evaluate the feature of neurons in the Meissner (submucosa) and Auerbach (muscular) plexus. Descriptive statistical analysis ANOVA and Tukey HSD were used to compare neuron indexes among groups.Results: The necrotic neuron index in the duodenal and ileal Auerbach plexus, including the degenerative neuron index in the jejunal Auerbach plexus, were significantly decreased with the EERbL-Np treatment at the dosages 60 and 90mg/kg.Conclusions: The 60 mg/kg EERbL-Np administration in the T2DM model may provide a neuroprotectant candidate in duodenal and ileal neuropathy. Dosage of 90mg/kg EERbL-Np is also promising in jejunal neuropathy treatment.